Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Perilaku Manajemen Keuangan pada Pelaku UMKM di Kabupaten Kolaka - Muh. Herdiansyah; Fitri Kumalasari; Niar Astaginy (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This research aims to determine: 1) The influence of financial literacy on financial management behavior among Small Medium Enterprise (SME) in Kolaka Regency. 2) The Influence of Financial Attitudes on Financial Management Behavior among SME owner in Kolaka Regency. This research is a research employed quantitative approach. Data collection of the research used observation, documentation and distribution of questionnaires. The population of this research is SME owner in Kolaka Regency. Meanwhile, the sample for this research consisted of 386 respondents using purposive sampling techniques, namely the technique of determining certain criteria. Research instrument testing used validity and reliability tests with SPSS 25.0. The data analysis technique used is measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 3.0. Based on the research results, it is known that the Financial Literacy variable has no influence on the Financial Management Behavior of SME owner. And the Financial Attitude variable has a positive and significant effect on Financial Management Behavior of SME owner.